The Influence of Lecturer-Student Interpersonal Communication on Student Learning Motivation in the UMMU KPI Study Program - Anjas Prasetyo; Salwa Muin; Siti Nur Alfiah A. (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study examines the dynamics of lecturer-student interpersonal communication and its influence on learning motivation in the Communication and Islamic Broadcasting Study Program at Muhammadiyah University of North Maluku. Interpersonal communication plays a crucial role in fostering students’ academic engagement and sustaining both intrinsic and extrinsic motivation. This research employed a qualitative approach using semi-structured interviews with two lecturers and five students, classroom observations, and document analysis. The data were analyzed through Miles and Huberman’s interactive model, involving data reduction, data display, and conclusion drawing. The findings show that lecturer-student communication develops through dynamic, dialogic, and interactive processes. Relationships that are characterized by openness, empathy, supportiveness, and equality create a positive learning atmosphere that strengthens students’ confidence, participation, and motivation. In addition, lecturers’ adaptive communication strategies, which consider individual student needs, contribute significantly to more effective learning interactions. The study concludes that interpersonal communication functions not only as a medium for delivering academic information but also as a strategic instrument for enhancing psychological safety and learning motivation. These findings highlight the importance of promoting supportive and participatory communication practices in higher education. Therefore, lecturers should maintain constructive interactions with students, while universities are encouraged to provide policies and professional development programs that strengthen communication competencies and create a more conducive learning environment.